2011
DOI: 10.1016/j.dnarep.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mcm10 interacts with Rad4/Cut5TopBP1 and its association with origins of DNA replication is dependent on Rad4/Cut5TopBP1

Abstract: 2Running title: Rad4 TopPB1 interacts with Mcm10 and associates with stalled replication forks. and Sld3 and to be required for the stable origin association of these two proteins. Rad4 TopBP1 chromatin association at stalled replication forks was found to be dependent upon the checkpoint protein Rad9, which was not required for Rad4 TopBP1 origin association. Comparison of the levels of chromatin association at origins of replication and stalled replication forks and the differential requirement for Rad9 sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Besides its essential role during replication initiation, Mcm10 is also required for DNA elongation and has been identified at replication forks by chromatin immunoprecipitation [5, 37]. Because Mcm10 interacts with the Mcm2-7 complex as well as Pol-α [2, 5, 1820, 30, 32–34, 38], it was proposed to link DNA unwinding and DNA synthesis [5].…”
Section: Structure and Function Of Mcm10mentioning
confidence: 99%
“…Besides its essential role during replication initiation, Mcm10 is also required for DNA elongation and has been identified at replication forks by chromatin immunoprecipitation [5, 37]. Because Mcm10 interacts with the Mcm2-7 complex as well as Pol-α [2, 5, 1820, 30, 32–34, 38], it was proposed to link DNA unwinding and DNA synthesis [5].…”
Section: Structure and Function Of Mcm10mentioning
confidence: 99%
“…Mcm10 was first identified in S. cerevisiae as a gene required for DNA replication 2,3 . Studies in different organisms from yeast to humans have shown that Mcm10 can interact with several replication initiation factors including Mcm2-7, 2,4-10 Cdc45, 11-13 TopBP1 14 and RecQ4 15-17 …”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, Mcm10 travels with the replication fork, pointing to a function in DNA elongation. 28,[32][33][34] Although roles for Mcm10 in origin unwinding, elongation and pol-α regulation are not mutually exclusive, the notion that Mcm10 is part of the eukaryotic replisome is a matter of ongoing debate in the field. 15,[18][19][20] Here, we exploited the fact that PCNA ubiquitination and DRIM can be utilized as a sensitive biological readout for the accumulation of ssDNA gaps.…”
Section: Introductionmentioning
confidence: 99%